Uji Ketahanan pH Minyak Atsiri dari Kulit Buah Jeruk dan Bunga Kenanga sebagai Bahan Pengganti Aromaterapi pada Mata Kuliah Perawatan Badan - Fitria Hansyah Fatmasari; Ria Andriani Mukti; Iut Nuraini (Journal on Education, 2023)
The formulation of the problem in this study tested the stability of the chemical content of essential oils from citrus fruit peels and ylang flowers. The aim of the study was to determine the feasibility of the chemical content in the essential oils of orange peel and ylang flowers. The research method used is laboratory tests and descriptive analysis in the collection and analysis of research data. The results of the study showed that the pH contained in essential oils was classified as acidic, so it could be used as aromatherapy. The conclusion of the research from the research that has been done needs further research related to the shelf life and durability of essential oils.